Aetiological factors in molar incisor hypomineralisation: a case-control study from Salamanca, Spain - Johanna Muñoz; Alfonso Alvarado-Lorenzo; Laura Criado-Pérez; Laura Antonio-Zancajo; Marta Muñoz-Bruguier; Adrián Curto (Italian Journal of Pediatrics)
Abstract Background Molar incisor hypomineralisation (MIH) is a developmental dental condition that causes defects in the enamel of the first molars and permanent incisors. The aim of the present study was to assess possible causal correlations between the mother-child dyad medical history and MIH. Methods An observational, retrospective, case‒control pilot study was carried out at the Dental Clinic of the University of Salamanca. This study was conducted between November 2023 and May 2024. Data on potential aetiological factors were collected through personal interviews, and the children’s parents were asked aetiological questions. Statistical analysis was performed with Student’s t test and the chi-square test. Results A total of 140 children were enrolled in the study. The case group included 70 children with MIH (31 boys and 39 girls; mean age: 9.1 ± 2.32 years), while the control group comprised 70 children without MIH (32 boys and 38 girls; mean age: 9.57 ± 3.09 years). Among the factors assessed, maternal drug allergies during pregnancy and childhood asthma were identified as potential aetiological contributors to MIH, both showing statistically significant associations (p < 0.01). Conclusions Within the limitations of this pilot case-control study, a potential association was observed between MIH and both maternal drug allergies during pregnancy and childhood asthma. These findings support the need for further investigation into prenatal and early-life factors that may contribute to enamel developmental disturbances. Larger prospective studies are recommended to confirm these associations and better understand the underlying mechanisms.